Synopsis: Grain price seasonality in Kebbi state, Nigeria - Hatzenbuehler, Patrick L.; Mavrotas, George; Maikasuwa, Mohammed Abubakar; Aliyu, Abdulrahaman (International Food Policy Research Institute, 2018)
Recent studies found the extent of food price seasonality in sub-Saharan Africa to be two to three times greater than that observed on global markets. This implies that, despite decades of market liberalization in many countries, there remains much progress to be made to improve general food marketing conditions throughout Africa. This issue deserves research because the movements of prices during a crop year influence the consumption decisions of households, the production decisions of farmers, and the marketing decisions of traders.